From broadcaster to National Media Network: Tracing Mediacorp’s evolution to a transmedia ecosystem - GENG, Xuesong (Institutional Knowledge at Singapore Management University, 2022)
Since early 2021, Mediacorp had started discussions and planning for its Mediacorp 2030 vision. Several new initiatives were proposed to deepen its digital evolution as it entered the digital era. While it had faced serious challenges from digital players about a decade earlier, Mediacorp has seen a steady increase in its digital revenue for the past several years. What have been the success factors for Mediacorp that enabled it to pull off this digital evolution? And what will be the new challenges it faces as it writes its next chapter? The case captures the decisions behind Mediacorp’s journey from a traditional media company to a transmedia company that integrates both traditional and digital business models. It first briefly reviews the history of Mediacorp as Singapore’s dominant broadcaster, as well as the challenges brought about by digital platforms like YouTube and Facebook about a decade ago. Next, the case charts Mediacorp’s evolution when it tried to adjust to the new digital environment. The final part of the case delves into how Mediacorp would scale up its 3P (Platform, IPs, and Personalities) and transmedia models to reinforce its competitive advantage and carry on the evolution momentum. The case provides material for readers to reflect on Mediacorp’s core, as well as its strengths and weaknesses. It then stimulates a discussion of the new challenges lying ahead, and how Mediacorp can get itself prepared to go from strength to strength. Students will learn about strategic change and digital transformation strategies in the media industry. They will analyse the industry’s strategic challenges; evaluate differences in business models between traditional and digital media, and the effectiveness of Mediacorp’s digital transformation strategies; examine the organisational factors influencing digital transformation; explore the strengths and weaknesses of Mediacorp's core business; and recommend ways to create competitive advantage.